Understanding Female STEM Faculty Experiences of Subtle Gender Bias from Microaggressions Perspective - Yang, Yang; Carroll, Doris W. (My University, 2016)
Research has repeatedly discussed the lack of women in many Science, Technology, Engineering, and Mathematics (STEM) fields. It has been suggested that the “chilly climate” - feeling unwelcomed or discriminated- pushes women away form STEM fields. This leads to many women leave STEM fields at multiple stages, thus the “leaking pipeline” explanation. The experiences of women who have stayed and are established in STEM fields are under examined. This study used microaggressions theory to understand STEM women’s experiences in academia. According to microaggressions theory, under represented groups, such as women in most male-dominant STEM disciplines, are likely to experience subtle bias and discrimination based on their identities. This study examined the degree to which women faculty in STEM disciplines experience subtle gender bias and whether such experiences differ based on their ranking, position track, age, and race/ethnicity. Participants included 57 women faculty in a broad range of STEM disciplines at ___ university. Both non tenure-track and tenure-track (including tenured) instructional and research faculty were included. The STEM disciplines chosen were so defined by the National Science Foundation (NSF, 2012). Subtle gender bias was measured by two instruments, which consisted of 29 items asking the extent to which participants agree with the statements regarding gender-based microaggressions events on a 7-point scale (1=Strongly disagree to 7=Strongly agree). The instrument included three aspects/factors of gendered microaggressions: (1) Sexual objectification (e.g., making a sexually inappropriate comment); (2) Silenced and marginalized (e.g., ignoring a woman’s opinions or comments in a workplace); (3) Assumptions of Inferiority (e.g., assuming women’s work would be inferior to men’s work). Participants were also asked about their position title, position track, age, and ethnicity. The scores on three aspects/factors of gendered microaggressions were calculated by averaging across items that loaded on each factor with the range of 1~7, with higher scores indicating experiencing sexual objectification. On Sexual objectification, the responses ranged from 1~6.75 (Mean = 2.83). 25% of the respondents agreed they experienced certain stereotypes of women and/or being objectified on their physical appearance (scored 4.01 or higher). On Silenced and marginalized, the responses ranged from 1~6.92 (Mean = 3.41). 59.6% agreed they have been ignored/invisible in a professional setting and/or been challenged regarding intelligence, authority (scored 4.01 or higher). Similarly, the responses ranged from 1.75~5.75 (Mean = 3.48) on Ascription of intelligence. 28.6% agreed they experienced being told women’s work would be inferior to men’s work and/or being told she is too assertive or sassy (scored 4.01 or higher). Furthermore, tenure-track respondents experienced more gendered microaggressions than non tenure-track respondents. Full professors experienced the most gendered microaggressions, followed by assistant professors, whereas instructors experienced the least. The oldest age groups experienced more gendered microaggressions than other ages. There is not much difference by ethnicity except one Native American respondent. This study provides a greater understanding of how women faculty perceive and encounter gender-based microagressions in various STEM fields. The results contribute to gender equity issues for the STEM disciplines where women are underrepresented and undervalued.
Citation: Yang,, Y. L., & Carroll, D. W. (2016, June), Understanding Female STEM Faculty Experiences of Subtle Gender Bias from Microaggressions Perspective Paper presented at 2016 ASEE Annual Conference & Exposition, New Orleans, Louisiana. 10.18260/p.27098